Basmajian-type inequalities for maximal representations - Fanoni, Federica; Pozzetti, Maria Beatrice (Arxiv, 2016)
For suitable metrics on the locally symmetric space associated to a maximal representation, we prove inequalities between the length of the boundary and the lengths of orthogeodesics that generalize the classical Basmajian's identity from Teichmueller theory. Any equality characterizes diagonal embeddings.